Performance analysis for reconfigurable intelligent surface assisted downlink NOMA networks - Xianli Gong; Chongwen Huang; Xinwei Yue; Feng Liu; Zhaohui Yang (IET Communications, 2022)
Abstract In this paper, a reconfigurable intelligent surface (RIS) assisted downlink non‐orthogonal multiple access (NOMA) network is considered, where a base station communicates with a pair of users with the assistance of a RIS. The performance of RIS‐assisted downlink NOMA networks is investigated by exploiting the coherent phase shifting design. In particular, the central limit theorem based Gaussian approximation is introduced to model the sum of independent and identically distributed random variables and derive the approximate expressions of the outage probability for two users. Furthermore, the upper bounds for the outage probability are obtained based on the property of the Bessel function. Additionally, both the asymptotic outage probabilities and the asymptotic upper bounds at high signal‐to‐noise ratio are derived and the diversity order achieved by the network is obtained. Simulation results are provided to validate the theoretical findings and demonstrate that RIS‐NOMA can achieve superior outage performance compared to RIS‐assisted orthogonal multiple access and conventional full‐duplex decode‐and‐forward relaying schemes. Moreover, it can be observed that the outage performance of RIS‐NOMA can be tremendously enhanced with increasing the number of reflecting elements.